2016
DOI: 10.5723/kjcs.2016.37.5.5
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution of Attachment Types and Their Characteristics in Middle Childhood Boys

Abstract: Sex differences in attachment are absent during infancy and early childhood, emerge in middle childhood with self-reports and doll-play tasks, and persist into adulthood, when they are most reliably detected in romantic attachment styles. In our previous work, we hypothesized that sex differences in attachment develop under the influence of adrenal androgens during the transition form early to middle childhood, following activation of hormone-sensitive neural pathways organized by prenatal and early postnatal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…The picture changes dramatically in middle childhood (about 6-11 years). Research has documented robust differences mirroring those observed in adulthood, with boys higher in avoidance and girls higher in preoccupation/ambivalence [2,[24][25][26][27][28][29][30]. This pattern has been replicated in North America, Europe, Israel, South Korea, and China, with dimensional scores from questionnaires and categorical classifications from doll-play tasks.…”
Section: Sex Differences In Childhoodmentioning
confidence: 79%
“…The picture changes dramatically in middle childhood (about 6-11 years). Research has documented robust differences mirroring those observed in adulthood, with boys higher in avoidance and girls higher in preoccupation/ambivalence [2,[24][25][26][27][28][29][30]. This pattern has been replicated in North America, Europe, Israel, South Korea, and China, with dimensional scores from questionnaires and categorical classifications from doll-play tasks.…”
Section: Sex Differences In Childhoodmentioning
confidence: 79%
“…Because of the decomposing organic matter in the groundwater may have occurred naturally or as a result of artificial sources. The potassium concentrations in groundwater ranged from 3-22 mg/L with an average of 1.30 mg/L showing the potential for sewage and fertilizer pollution of groundwater (Choi, 1988;Gedamy, 2015).…”
Section: Anthropogenic Activitymentioning
confidence: 99%